Mycorrhization of Lupinus spp. in nursery to improve the development of plants in ecological restoration strategies - Sandoval-García, Rufino; Alanís-Rodríguez, Eduardo; Astudillo-Sánchez, Claudia Cecilia; Mora-Olivo, Arturo (Revista Mexicana de Ciencias Agrícolas, 2025)
The species of the genus Lupinus are considered to be of great ecological and nutritional importance due to their ability to fix atmospheric nitrogen to the soil and to the high content of proteins (seeds), fibers (leaves), sugars (leaves), and minerals (seeds). The present study aimed to evaluate the development of Lupinus montanus and L. campestris as a response to seed mycorrhization. Inoculation was performed with Rhizophagus irregularis-BIOFertilizante INIFAP®. The treatments were 400 inoculated plants (200 per species) and 400 without inoculation, which were considered as controls. The variables evaluated were growth in basal diameter (mm), total height (cm), and nodule production one year after establishment. The experiment was conducted in January 2022 at the nursery of the Faculty of Forestry Sciences of the Autonomous University of Nuevo León, in Linares, Nuevo León, Mexico. The average growth in plants with mycorrhization showed a difference of 20% in basal diameter and 14% in height in L. montanus, whereas in L. campestris, it was 5% in basal diameter and 4% in height. In nodule production, a difference of 12.5% was observed in L. montanus and 28% in L. campestris compared to uninoculated seeds (control). The mycorrhization of the seeds had a significant impact (p< 0.001) on the development of Lupinus and its growth characteristics one year after its establishment. Both L. campestris and L. montanus are ideal for use in ecological restoration strategies because they generate beneficial microhabitats for the associated species.
Keywords: fixation of nitrogen; nurse plants; Rhizophagus irregularis; symbiosis